COGNITIVE FUNCTIONAL IMPAIRMENT IN POST-ISCHEMIC STROKE PATIENTS WITH HYPERTENSION - Hasan Nidlom; Eko Budi Santoso (International Journal of Social Science, 2025)
Stroke can cause functional brain disorders in the form of cognitive impairment. The incidence of cognitive impairment increases threefold after stroke, and usually involves impairment of visuospatial abilities, memory, orientation, language, attention, and executive function. This study used a cross-sectional method. The data obtained were analyzed descriptively (univariate), followed by a chi-square test for bivariate analysis, and logistic regression was used for multivariate analysis. The sample obtained was 110 samples, consisting of 72 men (65%) and 38 women (34.5%), with the most age group 51-60 years as many as 36 patients (32.7%). 75 patients (68.2%) experienced cognitive impairment (MoCA < 26) and 35 patients (31.8%) did not experience cognitive impairment (MoCA ≥ 26). Bivariate analysis found that hypertension (OR: 1.02; CI: 0.70-1.49; p: 0.823) did not affect the occurrence of cognitive impairment in post-stroke patients. Multivariate analysis found that the onset of recurrent stroke, the number of lesions, parietal lesions, and temporal lesions were associated with cognitive impairment after ischemic stroke. Hypertension was not associated with cognitive impairment in post-stroke patients